Polskie homilie Jana Pawła II – rekonesans badawczy - Zagórska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The article presents an overview of the Polish subject literature on the language of the homilies and speeches delivered by John Paul II. The second part of the article includes a discussion on the author’s own research study on the subject that takes into account the Pope’s use of one, autosemantic part of speech, the verb. The source material for the analysis has been excerpted from the homilies delivered by John Paul II in Polish during the Pope’s eight pilgrimages to his homeland. It includes homiletic texts from the years 1979, 1983, 1987, 1991, 1995, 1997, 1999 and 2002, i.e. from within the time bracket of 24 years. In 67 homilies, the Pope uttered 110,036 lexemes, which as a result of the analysis produced 1,787 verbal lexical units. The number of verbal lexeme formations amounts to 14,900. On average, one unit includes 225.75 verbal lexeme formations, whereas the average percentage share of verbal lexeme formations in the material under scrutiny is 13.54%.